Orientational pinning and transverse voltage: Simulations and experiments in square Josephson junction arrays - Marconi, V. I.; Candia, S.; Balenzuela, P.; Pastoriza, H.; Domínguez, D.; Martinoli, P. (American Physical Society, 2000)
Fil: Marconi, V. I. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina